2005
DOI: 10.1143/jjap.44.2905
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Stress Caused by Adsorption of O or N on Ga-terminated (100) GaAs Surface and InAl-terminated (100) InAlAs Surface: Degradation of Insulator/Semiconductor Interface

Abstract: Mechanical stress at the surfaces of GaAs and InAlAs, caused by adsorption of O or N on their group III surfaces, was calculated using small cluster models and first-principles calculations. These elements adsorb at the bridge sites and give strong compressive stress to the crystal. Assuming that only the O and N at the interface generate the stress, i.e., the insulator does not give any stress, mechanical stress at the insulator/semiconductor interface were calculated. N at the insulator/GaAs interface does n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2006
2006

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Increases in transconductance (g m ) and gate capacitance of GaAs-MISFET The reasons for the improvement in the crystallographic order are interpreted as a combination of the change of the interface bond structure from Ga-O to Ga-N and the annealing effect of the plasma. 6) The former removes strong mechanical stress at the interface, and enables the crystallographic order, which was degraded by oxidation, to recover by annealing.…”
Section: Effects Of Nitridation On Oxidized Gaas Surfacementioning
confidence: 99%
“…Increases in transconductance (g m ) and gate capacitance of GaAs-MISFET The reasons for the improvement in the crystallographic order are interpreted as a combination of the change of the interface bond structure from Ga-O to Ga-N and the annealing effect of the plasma. 6) The former removes strong mechanical stress at the interface, and enables the crystallographic order, which was degraded by oxidation, to recover by annealing.…”
Section: Effects Of Nitridation On Oxidized Gaas Surfacementioning
confidence: 99%
“…When the adsorption height at the bridge site is not quite different from the atomic layer distance of (100) GaAs (1.413 A), the adsobates do not cause a high stress, and hence such defects and disorder are not generated, as far as the critical thickness is not exceeded. Seto et al 10,16) reported that O adsorbs at the bridge sites of a Ga plane with an extremely low height (nearly zero) and generates a high stress, which very possibly generates defects or disorders, although whether the stress is accumulated or relaxed depends on the details of the bond structure between O and Ga. 16) Si and Ge, as well as S, Te, Se (passivation effect of these were reported), stably bind with the surface Ga or As atoms with heights of more than 1…”
Section: Ge 4s Ge 4pmentioning
confidence: 99%
“…Such defects and disorder are generated not only by the bombarding effect in processes such as implantation, sputtering and plasma and the decomposition of the semiconductor surface by a hightemperature process but also by mechanical stress associated with the atomic-level bond structure between the insulator and the semiconductor. 3) Oxidation of a GaAs surface using UV light and ozone generates a nm-order thin oxide layer, and it suppresses gate leakage current when such a layer is inserted between a channel and a gate electrode, 4) although this metal-oxide-semiconductor (MOS) gate does not always give sufficiently good performance in a metal-oxidesemiconductor field-effect transistor (MOSFET). 5) Process techniques for solving the problems have been experimentally studied, in order to fabricate usable MIS structures, using the deposition [6][7][8] and/or conversion methods.…”
Section: Introductionmentioning
confidence: 99%